2014
DOI: 10.1016/j.bbamcr.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Airway mesenchymal cell death by mevalonate cascade inhibition: Integration of autophagy, unfolded protein response and apoptosis focusing on Bcl2 family proteins

Abstract: HMG-CoA reductase, the proximal rate-limiting enzyme in the mevalonate pathway, is inhibited by statins. Beyond their cholesterol lowering impact, statins have pleiotropic effects and their use is linked to improved lung health. We have shown that mevalonate cascade inhibition induces apoptosis and autophagy in cultured human airway mesenchymal cells. Here, we show that simvastatin also induces endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) in these cells. We tested whether coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 75 publications
4
70
1
1
Order By: Relevance
“…This statin effect was not reversible with cholesterol co-treatment272851. It has been also shown that GGTI-298, but not FTI-277, can mimic the cytotoxic effects of statins, indicating that statins induce cell death by inactivating Rho/Rac GTPase activities52.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This statin effect was not reversible with cholesterol co-treatment272851. It has been also shown that GGTI-298, but not FTI-277, can mimic the cytotoxic effects of statins, indicating that statins induce cell death by inactivating Rho/Rac GTPase activities52.…”
Section: Discussionmentioning
confidence: 98%
“…For the proteolytic activity of caspase-8 (IETD-ase), -3/-7 (DEVD-ase), -9 (LEHDase), Caspase-Glo ® -3/-7, -8, and -9 (Promega) were determined in luminometric assays according to the manufacturer’s instructions and our previous report5187. Briefly, cells were grown in 96-well plate (15,000 cells/well) and treated with simvastatin (10 μM, 36 h).…”
Section: Methodsmentioning
confidence: 99%
“…neutrophils, eosinophils, lymphocytes, macrophages) [31,36,138], and reduce airway smooth muscle cell proliferation [43], oxidative stress [129], fibrosis [44], cytokine production [34,139], and mucus production [140]. The statins also induce apoptosis in cancerous or proliferative cells and airway mesenchymal cells [141], enhance macrophage efferocytosis [142], increase endothelial cell nitric oxide production [37], and improve cell barrier integrity [143]. …”
Section: Figurementioning
confidence: 99%
“…The product of HMG-CoA reductase activity, mevalonic acid, is a precursor of cholesterol and the isoprenoid intermediates farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP). Both FPP and GGPP play a central role in the process of prenylation, where FPP or GGPP are post-translationally added to a protein to facilitate cell membrane anchoring (Ghavami et al 2012(Ghavami et al , 2014Likus et al 2016). Isoprenoids are necessary for the post-translational modification of different proteins, such as GTPase proteins (Rho, Rac and Ras), which are important in many physiological processes.…”
Section: The Effect Of Statins On Mevalonate Pathwaymentioning
confidence: 99%